A Spectrophotometric Study of Complex Formation of Y3+, La3+ and Ce3+ with Some 18- and 15-Membered Crown Ethers in Methanol - Taheri, K.; Rounaghi, G.H.; Chamsaz, M.; Ansari Fard, M. (Asian Journal of Chemistry, 2010)
The complexation reactions between some rare earth metal cations (Ln =Y3+, La3+ and Ce3+) with 18-crown-6 (18C6), dicyclohexyl-18- crown-6 (DC18C6), decyl-18-crown-6 (Dec18C6), benzo-18-crown-6 (B18C6), benzo-15-crown-5 (B15C5) and N-phenylaza-15-crown-5 (PhN15C5) have been studied in methanol using a competitive spectrophotometric method. 2-(2-Thiazolylazo)-4-methyl phenol (TAC or L) was used as colorimetric complexant and the pH of solutions was fixed by hexamine/perchloric acid buffered system. The results show that the behaviour and stability of Ln-crown ether complexes are strongly affected by ring size, flexibility and substituent of crown ether ring, so that the complexes of 18C6 and DC18C6 with La3+ and Ce3+ cations are formed as 1:1, while those of Dec18C6 are formed as 1:2 in addition to 1:1 stoichiometry. Moreover, no evidence was observed for the interaction between B18C6, B15C5 and PhN15C5 with these cations in methanol solutions. It was found that the stability of Ln-crown ether as well as Ln-TAC complexes depends on pH of the solution. The stability constants of Ln-TAC complexes increase with increasing hexamine/perchloric acid concentration ratio, but in the case of Ln-crown ether complexes decrease. In addition, the results show that the complexation of Y3+ cation with all of the crown ethers is inappreciable in this solution.